Development of boxprob teaching aid for mathematics learning probability material - Shahrul Khan, Mohamad Ilham; Wahid, Sirojudin; Handoko, Hendri (Pusat Studi Pengembangan Pembelajaran Matematika, 2026)
This research is a development research of BOXPROB teaching aids for Mathematics learning on probability material for junior high school students. The objectives of this research are to: (1) produce valid BOXPROB teaching aids for Mathematics learning on probability material for junior high school students, (2) analyze the practicality of these teaching aids, and (3) determine whether these teaching aids can improve the learning outcomes of junior high school students. This research uses a Research and Development (R&D) approach consisting of three stages, namely (1) defining (define), (2) designing (design), and (3) developing (develop). The subjects of the research were students of class VIII F of SMP Negeri 16 Cirebon City. Data collection techniques were carried out through observation, questionnaires, and learning outcome tests. For data analysis, analysis of the validity of teaching materials and data analysis of the practicality of teaching materials were used. The results of the research show that the developed learning aids: (1) are valid after going through the validation process, (2) are practical based on positive responses from students regarding the BOXPROB teaching aids for Mathematics learning on probability material, and (3) can improve the learning outcomes of Junior high school students in Mathematics learning on probability material.